INCIDENCE OF POSTPARTUM ANEMIA AMONG POSTPARTUM PATIENTS IN EAST JEDDAH HOSPITAL: Pharmaceutical Science-Gynecology - MATTAR, GHADEER; ALSAHAFI, NADA; BAYADER SHAMI; ABULKHAIR, SUMYAH; ALHAZMI, NADIA; ALSALEH, REHAB (International Journal of Life Science and Pharma Research, 2019)
Postpartum anemia (PPA) is an important health problem affecting women at Saudi Arabia, which increase the risk of maternal mortality and morbidity. There are many risk factors which can affect the incidence of postpartum anemia. In our study we shed the light on the incidence and the risk factors associated with this among patients who delivers in EJH. This study is retrospective cohort study for patients delivered at EJH from first of January 2018 to 30 of June 2018. The total number of cases is 1252, who had complete data and others were excluded. However, during the analysis, we just analyzed 250 cases. In our study, we selected definition of PPA is having Hb < 10 g/dl on day 1 after delivery. Our study showed that incidence of PPA is round 60% which is high in comparison with international figure (22-45 %). These findings shed the light on the urgent need to keep PPA monitor to adjust current strategies to control risk factors associated with PPA. There was a significant correlation between postpartum anemia and blood transfusion. Preterm gestational age, cesarean delivery, antenatal anemia were significant independent risk factors for postpartum anemia. It was found that postpartum anemia (PPA) was higher among those delivered through cesarean delivery and low among those delivered through vaginal route. So, we recommended to increase the patient awareness about risks associated with cesarean delivery and to have sufficient control on cesarean delivery by request. Antenatal anemia was significant risk factor for PPA. It might be due to poor nutritional quality of mothers and poor intake of iron therapy. PPA was less associated with postpartum complications as all of these complications due to vaginal deliveries and all cases who needed blood transfusion were diagnosed with postpartum anemia